2020
DOI: 10.7717/peerj.9943
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an 8-miRNA signature as a potential prognostic biomarker for glioma

Abstract: Background Glioma is the most common form of primary malignant intracranial tumor. Methods In the current study, miRNA matrix were obtained from the Chinese Glioma Genome Atlas (CGGA), and then univariate Cox regression analysis and Lasso regression analysis were utilized to select candidate miRNAs and multivariate Cox regression analysis was applied to establish a miRNA signature for predicting overall survival (OS) of glioma. The signatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…51,52 Finally, as regards Rhas4, hsa-miR-1246 has been also described as a potential prognostic biomarker for glioma, being predicted as one of its target genes. 53 In addition to ACE2 and RAB14, another 2,810 target genes were predicted for our 4 miRNAs. Overall, our in silico analysis indicated that these miRNAs are much more than simple post-transcriptional regulators since, besides, they have been involved in several biological processes related to the pathogenesis of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 93%
“…51,52 Finally, as regards Rhas4, hsa-miR-1246 has been also described as a potential prognostic biomarker for glioma, being predicted as one of its target genes. 53 In addition to ACE2 and RAB14, another 2,810 target genes were predicted for our 4 miRNAs. Overall, our in silico analysis indicated that these miRNAs are much more than simple post-transcriptional regulators since, besides, they have been involved in several biological processes related to the pathogenesis of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 93%
“…Bene t from the rapid development of microarray and high-throughput sequencing technology, increasing potential biomarkers that contributed to disease progression have been identi ed (Ni et al, 2018;Zhou, Tang, Liu, An, & Zhang, 2017). Several large and free public transcriptome databases, including GEO, TCGA, and CGGA databases, provide valuable gene expression data for the identi cation of potential biomarkers that related to diagnosis, prognosis or phenotype, and the construction of genome-wide coexpression networks, and the study of molecular mechanisms of pathogenesis (Hu et al, 2019;Ji et al, 2020). The weighted gene co-expression network analysis (WGCNA) is widely used in disease and other traits and gene association analysis, as it has the capacity of clustering genes with similar expression patterns and analyzing the relationship between modules and speci c traits or phenotypes (Langfelder & Horvath, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, miRNAs have been accepted as potential diagnostic markers or prognostic biomarkers for diseases of different organs. For example, a recent study developed a novel prognostic signature that excellently predicted the 1-and 3-year survival rate of patients with glioma (45). Another study on pancreatic cancer established a risk score system using 7 miRNAs to predict overall survival and recurrencefree survival, which showed reliable performance with a high C-index (46).…”
mentioning
confidence: 99%